Rwanda : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the processes involved in the financial stability of Rwanda after the global crisis are imparted. High growth and major risks included in macroeconomic stability are analyzed. In the case of the banking sector, the structure, performance, and competition of Rwandan banks are outlined. The steps to strengthen regulation and supervision of banks are included in this study. Systemic liquidity management, payment system, and insolvency and creditor rights are explained under financial structure infrastructure. Issues related to the development of housing, pension, and insurance are also discussed.